2017
DOI: 10.30737/ekonika.v1i1.7
|View full text |Cite
|
Sign up to set email alerts
|

Peran Kualitas Produk, Harga Dan Kualitas Layanan Terhadap Kepuasan Pelanggan Billagio Skincare Clinic Sidoarjo

Abstract: AbstrakBisnis di bidang perawatan kecantikan dewasa ini telah berkembang pesat seiring dengan kemajuan jaman di indonesia, salah satu perusahaan tersebut adalah Billagio Skincare Clinic Sidoarjo. Namun seiring kemajuan tersebut terjadi fenomena penurunan pendapatan dan meningkatnya komplain pelanggan. Penelitian ini bertujuan untuk mengetahui pengaruh kualitas produk, harga dan kualitas layanan terhadap kepuasan pelanggan Billagio skincare clinic Sidoarjo. Dalam penelitian ini menggunakan variabel kualitas pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
7
0
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 0 publications
3
7
0
9
Order By: Relevance
“…This means that the results of this study indicate that prices have no effect on customer satisfaction. The result of this study is supported by research findings from Bilgies (2016), which states that prices have no significant effect on customer satisfaction. Related to the results of the study, which stated that prices did not have a significant effect, it was because there was a possibility of respondents' assumption that the price between fellow online transportation did not have a significant difference.…”
Section: Relationship Between Price and Customer Satisfactionsupporting
confidence: 77%
See 2 more Smart Citations
“…This means that the results of this study indicate that prices have no effect on customer satisfaction. The result of this study is supported by research findings from Bilgies (2016), which states that prices have no significant effect on customer satisfaction. Related to the results of the study, which stated that prices did not have a significant effect, it was because there was a possibility of respondents' assumption that the price between fellow online transportation did not have a significant difference.…”
Section: Relationship Between Price and Customer Satisfactionsupporting
confidence: 77%
“…Based on those modification explanations, then the purpose of this study is to find out whether price, service quality, and trust influence the satisfaction of online transportation customers. In addition, through this study, it is expected to be able to re-test specifically for the contrasting findings gap by Bilgies (2016), Isra and Trenggana (2017) regarding their research results that found variables and service quality have no significant influence on customer satisfaction. In detail, Bilgies (2016) who found that price variable has no influence on customer satisfaction, while she conducts a study on beauty care clinic that not only sell products but are also supported by experienced doctors and beauticians to give optimum result's service (Billagio, 2018).…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…Penelitian ini mendukung 2 penelitian terdahulu yang dilakukan oleh Indrawati (2017) dan Bilgies (2016) yang menyatakan bahwa variabel kualitas pelayanan berpengaruh secara signifikan terhadap kepuasan pelanggan di Toko Mukena Al-Kharimah Rejotangan Tulungagung dan Billagio Skincare Clinic Sidoarjo. Hasil penelitian ini sesuai dengan penelitian yang dilakukan di Gatherinc Bistro & Bakery Surabaya dikarenakan semakin baik pelayanan yang diberikan dan sesuai dengan harapan konsumen maka semakin tinggi pula kepuasan pelanggan.…”
Section: Variabel Store Atmosphere Terhadap Kepuasan Pelangganunclassified
“…, kualitas produk (Hidayat, 2009;Markoni, 2011;Suputra dan Mandala, 2014;Suwarni dan Mayasari, 2014), dan harga yang ditawarkan (Worodiyanti dan Maspiyah, 2016;Bilgies, 2016;Prasetio, 2012;Saputra, 2015…”
unclassified